2015
DOI: 10.1016/j.jep.2015.03.080
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical evidences of Pyrostegia venusta in the treatment of vitiligo

Abstract: For the first time these data show that topical and oral administrations of P. venusta have significant antiinflammatory and hyperpigmentant effects, demonstrating different topical and systemic effects through two animal models. Together these models are capable to mimic several features founded in vitiligo, and the results support the ethnopharmacological use of P. venusta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
4
0
3
Order By: Relevance
“…To investigate the effect of this extract in animal models of vitiligo, the hyperpigmentant activities of HE in C56BL/6 mice was also studied later by Moreira et al [ 44 ]. The results showed that extract administered either by gavage (300 mg/kg) ortopically (10%) increased epidermal melanin level (116.5 ± 13% and 100 ± 16.9%, respectively), diminished dermal depigmentation (36.0 ± 6.7% and 38.2 ± 6.2%, respectively), as well as tissue TNF-α levels (68.2 ± 11.6% and 99.2 ± 12.1%, respectively) and cell infiltration (basal levels and 94.3 ± 9.17%, respectively).…”
Section: Melanogenesis Stimulators From Different Sourcesmentioning
confidence: 99%
“…To investigate the effect of this extract in animal models of vitiligo, the hyperpigmentant activities of HE in C56BL/6 mice was also studied later by Moreira et al [ 44 ]. The results showed that extract administered either by gavage (300 mg/kg) ortopically (10%) increased epidermal melanin level (116.5 ± 13% and 100 ± 16.9%, respectively), diminished dermal depigmentation (36.0 ± 6.7% and 38.2 ± 6.2%, respectively), as well as tissue TNF-α levels (68.2 ± 11.6% and 99.2 ± 12.1%, respectively) and cell infiltration (basal levels and 94.3 ± 9.17%, respectively).…”
Section: Melanogenesis Stimulators From Different Sourcesmentioning
confidence: 99%
“…Assim, observou-se no relato de caso de Jha (2020), um paciente que utilizou uma mistura de sementes trituradas de bakuchi (Psoralea corylifolia) e óleo de coco, em seguida expôs a pele ao sol por 5 minutos, com instruções de um vídeo numa plataforma midiática conhecida. Paralelamente, um ensaio pré-clínico realizado em camundongos com edema de orelha induzido por óleo de cróton mostrou que o extrato hidroetanólico de folhas de P. venusta por gavage (300 mg/kg) reduziu a atividade da N-acetil-b-d-glucosaminidase (NAG) (32,5±5%), a infiltração celular (42,3±5,9%), os níveis de interleucina-1β (IL-1β)(44,1±9,7%), interleucina (IL-6) (71,9±22,2% ) e fator de necrose tumoral-α (TNF-α) aos níveis basais (MOREIRA et al, 2015).…”
Section: Resultsunclassified
“…Pyrostegia venusta (also known as “cipó – de – são - joão”) is a herb of the family Bignoniaceae, widely distributed in southern Brazil, where topical formulations are commonly used for the treatment of vitiligo. Even if its mechanisms of action are still under investigations, the herb seems to be effective for its antioxidant, anti-inflammatory and melanogenic properties [ 34 ].…”
Section: Pyrostegia Venustamentioning
confidence: 99%